Grain size analyses and organic matter content of bottom sediment sampled along the French Mediterranean coast in 2015 - Parent, Briz; Barras, Christine; Maillet, Grégoire M; Jorissen, Frans J (PANGAEA, 2021)
The stations were sampled along the French Mediterranean coast in spring (March-April) 2015 onboard the RV Europe. Bottom sediment at 28 stations (11 to 64 m water depth) was sampled using a Reineck box-corer. Three replicates (“a”, “b”, “c”; different box-corer launches) were done at each station for meiofauna analysis. Surface sediment (0-1 cm) from the first box-corer launch (i.e., “a”) was sampled and put into plastic bags. If the sediment appears visually very different in the second and/or third launches (i.e., “b” and “c”) another sample was taken. At the laboratory, three aliquots of each sample were homogenised with a mixer mill, without ball, at 17 Hz for 2 min. Then, aliquots were sieved on a 2 mm mesh and analysed with a Malvern Mastersizer 3000 for grain size analysis. Three measures were performed for each aliquot. The organic matter percentage was determined with the loss on ignition method, 4h30 at 450 °C. These data were acquired thanks to Pierre Boissery and the funding from the Agence de l'Eau Rhône Méditerranée Corse. The sampling survey was possible thanks to the Ifremer, especially Bruno Andral, and the RV Europe crew members.
Keywords: Grain Size; Grain size data; grain size distribution; laser particle sizer; loss on ignition; Mediterranean; organic matter